USTADZAH FASHION STYLE AS NONVERBAL COMMUNICATION AT THE AL-IMAN PUTRI PONDOK PESANTREN PONOROGO - Majidah, Ismi Qomariyatul (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Fashion Style is a form of nonverbal communication. The clothes a person wears can interpret themselves as well as show personality characteristics. The purpose of this study is to explain the purpose of using ustadzah Fashion Style at Al-Iman Putri Ponorogo Islamic Boarding School, and analyze the meaning of Fashion Style used by ustadzah as a means of Nonverbal Communication at Al-Iman Putri Ponorogo Islamic Boarding School. The research method used is a qualitative approach with a descriptive method. Research data was collected by conducting interviews with informants, namely ustadzah Pondok Pesantren Al-Iman Putri who had qualifications as ustadzah who looked attractive and followed fashion trends. The results showed that the use of fashion to communicate nonverbally about his identity. Everyone tries to show their best side and unique side of themselves through the fashion they wear. Ustadzah Pondok Pesantren Al-Iman Putri uses fashion style with the goal: easier to identify, convey a form of self-expression, and the purpose of beauty. Nonverbal Communication through fashion style ustadzah Pondok Pesantren Al-Iman Putri Ponorogo is considered effective because it produces communication results. And from the fashion style displayed, they try to convey their identity, character, class and group.